2017
DOI: 10.1080/15476286.2017.1391444
|View full text |Cite
|
Sign up to set email alerts
|

What makes ribosomes tick?

Abstract: In most organisms, gene expression over the course of the day is under the control of the circadian clock. The canonical clock operates as a gene expression circuit that is controlled at the level of transcription, and transcriptional control is also a major clock output. However, rhythmic transcription cannot explain all the observed rhythms in protein accumulation. Although it is clear that rhythmic gene expression also involves RNA processing and protein turnover, until two years ago little was known in any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…This does not exclude that oscillating mRNAs also contribute to the regulation of non‐fluctuating proteins if the degradation and synthesis rates of these proteins are changing during the diurnal cycle. In Arabidopsis, there is increasing evidence of diurnal and photoperiodic dynamics of mRNA translation (Mills, Enganti, & von Arnim, 2018; Seaton et al, 2018). If dynamic regulation of protein degradation and synthesis is coupled to differential ribosomal loading of oscillating mRNAs, this would result in stable diurnal protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…This does not exclude that oscillating mRNAs also contribute to the regulation of non‐fluctuating proteins if the degradation and synthesis rates of these proteins are changing during the diurnal cycle. In Arabidopsis, there is increasing evidence of diurnal and photoperiodic dynamics of mRNA translation (Mills, Enganti, & von Arnim, 2018; Seaton et al, 2018). If dynamic regulation of protein degradation and synthesis is coupled to differential ribosomal loading of oscillating mRNAs, this would result in stable diurnal protein levels.…”
Section: Resultsmentioning
confidence: 99%
“…In the brain of Drosophila , expression of the Tor gene shows a bimodal pattern in light/dark cycles, and rhythmic changes in neuron morphology depend on expression of Tor [ 52 ]. An important output of the clock is gene expression; the role of the circadian clock in regulating gene transcription is well known, and recent findings have shown that the clock is also able to regulate specific genes at the level of translation in several organisms [ 53 , 54 ] including Neurospora [ 55 ]. The TOR pathway can play a role in this translational regulation: in mouse cells, mTORC1 activity is rhythmic [ 56 ], which drives rhythmic phosphorylation of 4E-BP1 and rhythmic translation of proteins [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ribosome loading of mRNAs is also under the control of the circadian clock, as indicated by broad changes in the phase and amplitude of diel translation in a clock-deficient strain. The mRNAs for ribosomal proteins are among those with the most pronounced and coordinated changes in diel ribosome loading ( Missra et al, 2015 ; Mills et al, 2017 ). These findings indicate that signals from the light environment and signals from the circadian clock must be integrated as they converge onto the translation apparatus.…”
Section: Introductionmentioning
confidence: 99%